OxLDL induces vascular endothelial cell pyroptosis through miR‐125a‐5p/TET2 pathway. Issue 5 (28th October 2018) - Zhaolin, Zeng; Jiaojiao, Chen; Peng, Wu; Yami, Liu; Tingting, Zhang; Jun, Tao; Shiyuan, Wu; Jinyan, Xiao; Dangheng, Wei; Zhisheng, Jiang; Zuo, Wang
Abstract: Pyroptosis participates in the formation and development of atherosclerosis (As) by promoting inflammatory factor release and is closely related to the stability of atherosclerotic plaque. MicroRNAs can regulate the expression of target genes at the posttranscriptional level. Previous studies have shown that miR‐125a‐5p increases in hyperlipidemic–hyperglycemic conditions and is involved in apoptosis, but its specific role in pyroptosis and As remains unclear. We propose that miR‐125a‐5p may be implicated in oxidized low‐density lipoprotein (oxLDL)‐induced vascular endothelial cells (VECs) pyroptosis and therefore conducted the current study. We observed that miR‐125a‐5p can inhibit tet methylcytosine dioxygenase 2 (TET2) expression at the posttranscription level, resulting in abnormal DNA methylation, mitochondrial dysfunction, and increased reactive oxygen species production, activated nuclear factor‐κB that induces activation of inflammasome and maturation, release of proinflammatory cytokines interleukin (IL)‐1β and IL‐18, and pyroptosis. Given the role of VECs in vascular physiology, oxLDL‐induced VEC pyroptosis may promote the development of As. Our current study reveals a novel pathway associated with pyroptosis program regulation, which comprises miR‐125a‐5p and TET2 in VECs. Modulation of their expression levels may serve as a potential target for therapeutic strategies of As. Abstract : In this study, we revealed that miR‐125a‐5p mediates oxidized low‐density lipoprotein (oxLDL)‐induced pyroptosis in the vascular endothelial cell (VECs) by downregulating tet methylcytosine dioxygenase 2 (TET2). TET2 suppression will increasing nuclear factor‐κB (NF‐κB) activation, activating NLRP3 and caspase‐1, and ultimately causing pyroptosis of VECs. After TET2 downregulation, abnormal DNA methylation will occur, and subsequently, mitochondrial dysfunction will induce reactive oxygen species (ROS) production, which activates NLRP3 inflammasome, leading to the activation of caspase‐1. Activated caspase‐1 triggers pore formation of the membrane, DNA fragmentation, and release of mature interleukin (IL)‐1β and IL‐18 from cells, causing a sterile inflammation response and further contributing to pyroptotic cell death and subsequently promoting atherosclerosis.